1996
DOI: 10.1002/hep.510230413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glyceraldehyde-3-phosphate dehydrogenase and 28S-ribosomal RNA gene expression in human hepatocellular carcinoma

Abstract: The gene responsible for transcribing glyceraldehyde-and integrity of RNA present in Northern analyses. 3-phosphate dehydrogenase (GAPDH) is commonly used Whether the GAPDH gene can be used for the same as a reporter gene to estimate the amount of RNA pres-purpose in tumor cell lines or tissues is unclear. Indeed, ent in Northern analyses. However, recent data suggest there are numerous reasons to suspect that GAPDH that GAPDH gene expression may vary with the extent messenger RNA (mRNA) expression may not be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 5 publications
2
38
0
Order By: Relevance
“…Previous studies have shown that GAPDH expression is increased in other human tumors and tumor-derived cell lines from colon, kidney, liver, lung and pancreas (Nguewa et al, 2008;Lau et al, 2000;Gong et al, 1996;Chang et al, 2011;Revillion et al, 2000;Yamagata et al, 1998), which complies with our results. Because of the variability of expression of GAPDH in osteosarcomas, GAPDH expression should not be used as housekeeping genes in analyses on mRNA level and protein level in osteosarcomas studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have shown that GAPDH expression is increased in other human tumors and tumor-derived cell lines from colon, kidney, liver, lung and pancreas (Nguewa et al, 2008;Lau et al, 2000;Gong et al, 1996;Chang et al, 2011;Revillion et al, 2000;Yamagata et al, 1998), which complies with our results. Because of the variability of expression of GAPDH in osteosarcomas, GAPDH expression should not be used as housekeeping genes in analyses on mRNA level and protein level in osteosarcomas studies.…”
Section: Discussionsupporting
confidence: 93%
“…Because of the variability of expression of GAPDH in osteosarcomas, GAPDH expression should not be used as housekeeping genes in analyses on mRNA level and protein level in osteosarcomas studies. The elevation of GAPDH mRNA level or protein level might accelerate the malignant cell proliferation, since enhanced expression of GAPDH was accompanied by an increase in the levels of enolase and glucose transporter and an accelerated rate of glucose transport has long been known to accompany cellular transformation (Gong et al, 1996). The up-regulation of GAPDH in tumor could contribute to augmented rate of glycolysis in tumor cells and/or maintenance of a transformed phenotype (Vila et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, GAPDH expression can be modulated by the cell proliferative state, and GAPDH can be overexpressed in some cancers (Gong et al, 1996;Cuezva et al, 2004) and in neurodegenerative disorders such as Hungtington, Parkinson and Alzheimer diseases (Mazzola and Sirover, 2002). Moreover, GAPDH antisense rescues cerebellar and mesencephalic dopaminergic neurons from cell death induction in vitro Fukuhara et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…GAPDH has been widely used as a reference gene in RT-qPCR analysis performed in HCC cells; however, elevated mRNA and protein expression levels of GAPDH in HCC patients have been reported in a number of studies (30,31). These studies investigated patients with HBV-associated HCC, hepatitis C virus-associated HCC and HCC without viral hepatitis infection history.…”
Section: Discussionmentioning
confidence: 99%